Ureteral Rupture Caused by Accidental Intubation of the Ureter with a Foley-Catheter during Ureterorenoscopy - F. Löcherbach; P. Grimsehl; A. Sauer; S. Wyler; M. Kwiatkowski (Case Reports in Urology)
We would like to present the case of a 64-year-old woman who underwent ureterorenoscopy and suffered an iatrogenic ureteral lesion due to an accidental intubation of the left ureter with a Foley-Catheter during the procedure. A Double-J-Stent was implanted into the damaged ureter, and 6 weeks later it fully recovered. To our knowledge there are few similar cases described in the literature with none of those having happened during ureterorenoscopy so far.